2004
DOI: 10.1523/jneurosci.1150-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

YB-1 and CTCF Differentially Regulate the 5-HTT Polymorphic Intron 2 Enhancer Which Predisposes to a Variety of Neurological Disorders

Abstract: The serotonin transporter (5-HTT) gene contains a variable number tandem repeat (VNTR) domain within intron 2 that is often associ-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
72
2
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 46 publications
8
72
2
1
Order By: Relevance
“…In addition to VNTR copy number, the different primary DNA sequence of the VNTR elements that constitute the VNTR can support differential reporter gene expression (Lovejoy et al, 2003). Our most recent report has demonstrated that the SLC6A4 intron 2 VNTR is bound and regulated by the transcription factor Y-box binding protein 1 (YB-1) (Klenova et al, 2004) a member of the Y-box binding proteins (Wolffe et al, 1992;Wolffe, 1994;Swamynathan et al, 2002;Kohno et al, 2003), and this regulation is modulated by the transcription factor CCCTC binding protein (CTCF) (Klenova et al, 2004), a known binding partner of YB-1 (Chernukhin et al, 2000). CTCF, in addition to transcriptional activation or silencing in a context-dependent manner, organizes epigenetically controlled chromatin insulators regulating imprinted genes (Klenova et al, 1993;Filippova et al, 1996;Ohlsson et al, 2001;Klenova et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to VNTR copy number, the different primary DNA sequence of the VNTR elements that constitute the VNTR can support differential reporter gene expression (Lovejoy et al, 2003). Our most recent report has demonstrated that the SLC6A4 intron 2 VNTR is bound and regulated by the transcription factor Y-box binding protein 1 (YB-1) (Klenova et al, 2004) a member of the Y-box binding proteins (Wolffe et al, 1992;Wolffe, 1994;Swamynathan et al, 2002;Kohno et al, 2003), and this regulation is modulated by the transcription factor CCCTC binding protein (CTCF) (Klenova et al, 2004), a known binding partner of YB-1 (Chernukhin et al, 2000). CTCF, in addition to transcriptional activation or silencing in a context-dependent manner, organizes epigenetically controlled chromatin insulators regulating imprinted genes (Klenova et al, 1993;Filippova et al, 1996;Ohlsson et al, 2001;Klenova et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CTCF interactions with Sin3 (37) and YB-1 (10,28) are shown to modulate CTCF function as a transcriptional repressor. The cooperation of CTCF with nucleophosmin (68), Kaiso (13), and helicase protein CHD8 (22) has been linked to the control of insulator function of CTCF and epigenetic regulation.…”
mentioning
confidence: 99%
“…For example, the minisatellite located in intron 2 of the serotonin transporter gene 5-HTT may influence its transcription levels by binding the transcription factor YB-1 (Klenova et al, 2004). The location of minisatellites involved in the regulation of gene expression and function need not be limited to promoter sequences.…”
Section: Minisatellite Loci In Human Dnamentioning
confidence: 99%